PREMATURE SKIN AGEING: CLINICAL AND MORPHOLOGICAL CHARACTERISTICS - Makhmatkulova G. M. (Scholar Express Journal, 2024)
During the human existence, the skin undergoes a strong process of morphological, structural and biochemical changes, which are manifested by thinning, inconsistent tone, hyperpigmented patches spots, loss of flexibility and decreased turgor
Keywords: Chronological skin ageing; turgor; wrinkles